Genetic diversity and distinctness based on morphological and SSR markers in peanut. (10th August 2021) - Hong, Yanbin; Pandey, Manish K.; Lu, Qing; Liu, Hao; Gangurde, Sunil S.; Li, Shaoxiong; Liu, Haiyan; Li, Haifen; Liang, Xuanqiang; Varshney, Rajeev K.; Chen, Xiaoping
Abstract: The morphological and molecular diversity of 101 peanut varieties from South China were analyzed to identify distinctness among these varieties. No significant difference was observed for six morphological characteristics whereas a range of 0.25–0.51 of diversity index was observed for 11 morphological characteristics, with an average value of 0.39. Molecular characterization with 40 highly polymorphic simple sequence repeats (SSRs) generated a total of 167 alleles ranging from two to six alleles per marker with average 4.18 alleles per marker. The polymorphism information content (PIC) of these markers varied from 0.79 to 0.26 with an average value of 0.55 per marker. The diversity analysis using morphological and genotyping data grouped all the varieties into seven and six clusters, respectively, and varieties released by the same province tended to be grouped in the same cluster. Mantel testing revealed that the correlations between the similarity coefficient matrixes of the morphological characteristics and SSR markers of different varieties were weak ( r = .347), implying that deployment of more SSR markers is needed for achieving distinctness among these peanut varieties. Nevertheless, the combination of morphological characteristics and SSR markers will effectively increase the accuracy of distinctiveness identification. Core Ideas: A range of 0.25–0.51 of diversity index was observed for 11 morphological features. Morphological and genotyping data grouped all the varieties into seven and six clusters. Deployment of more SSR markers is needed for achieving distinctness among peanut varieties.